CO2 Emissions and Subjective Well-Being: Empirical Evidence from The Southeast Asian Population - Priyanto, Moh. Wahyudi; Wijayanti, Dian Eswin; Hilmi, Yahya Shafiyuddin (Muhammadiyah University Press, 2024)
An increasing amount of carbon dioxide (CO2) affects the planet and people. As a primary contributor to climate change, CO2 has been a subject of discussion among researchers. Many have been studying the complex relationship and impact of CO2. However, a study examining the influence of increased CO2 emissions on human subjective well-being is limited. This study aims to fill the gap by utilizing a sample of 9,724 Southeast Asians from the Seventh World Values Survey (2017-2021). Well-being is measured using a subjective approach, such as happiness and life satisfaction. The ordered probit regression analysis indicates that increased per capita CO2 emissions decrease happiness and life satisfaction. Additionally, the higher individuals' financial and health levels, the higher their relationship with their happiness and life satisfaction will be. This study encourages further research investigating a specific country's relationship between CO2 emissions and the well-being of its population.